COMPATIBILITY OF A MARRIED COUPLE BY ROLE POSITIONS AND FAMILY VALUES AS A FACTOR IN THE SATISFACTION OF SPOUSES WITH MARRIAGE - L. A. Kostina; M. A. Sergeeva; T. A. Smakhtina; A. S. Kubekova (Вестник университета)
The results of research on the compatibility of a married couple by role positions and family values as a factor in the satisfaction of spouses with a marriage have been presented. The following psychodiagnostic methods were used as research methods: the test “Role positions in interpersonal relationship” by E. Burn, the questionnaire “Role expectations and claims in marriage” (A. N. Volkova), the method of V. Stolin “Test satisfaction survey marriage”. As methods of statistical analysis, the Mann-Whitney U-test was used to identify significant differences in all parameters of the four formed groups. It was found that satisfaction with marriage directly depends on the compatibility of marriage partners in role positions and family values. As a consequence, couples in which the spouses are compatible on two possible factors are more satisfied with their relations, while spouses whose role positions are incompatible and family values are not agreed are least satisfied with the marriage. The obtained results can be used in the practical work of psychologists.